Prekrivanke v slovenščini z vidika vpliva angleškega jezika - Sicherl, Eva (Jezik in slovstvo, 2018)
The article aims to present the phenomenon of blends in Slovene. It discusses the influence of English on the formation of such coinages in Slovene. A typology of blends for Slovene is proposed, based on some already established linguistic theories created for other languages. The proposed typology also provides criteria for the inclusion of blends as a specific type of word-formation process in Slovene. A distinction is made between blends imported into Slovene and Slovene-made blends, with the latter type based on the already established word-formation process of juxtaposition.
Keywords: angleščina; krnitev; prekrivanke; sklapljanje; slovenščina